Union of Comoros - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
The Union of Comoros remains at moderate risk of external debt distress, but its space to absorb shocks is “limited.” All debt burden indicators exhibit a continual upward trend, with the PV of debt-to-export approaching its threshold at the end of the assessment horizon (2029) under the baseline scenario. (Thresholds reflect “medium” capacity to carry debt). The reduced space to absorb shocks reflects the taking on of a large new loan, a downward revision of projected exports in line with lower export prices and impacts of Cyclone Kenneth on debt accumulation. Shock scenarios indicate vulnerability to a deterioration of export performance, natural disasters, and exchange rate instability. Comoros’ overall risk of debt distress remains moderate, given that domestic debt is expected to remain minimal. The authorities need to strengthen policies to improve macroeconomic performance including by making faster progress on domestic resource mobilization and broadening the export base. The authorities should proceed cautiously on taking up any new debt and may wish to largely avoid new non-concessional debt.